DETECTION OF 41Ar IN THE VICINITY OF PAKISTAN RESEARCH REACTOR – 1 DURING 2007-2009 - Wasim, M.; Zaidi, J. H.; Arif, M.; Anwar, Y. (The Nucleus, 2020)
The study reports the determination of 41Ar in the vicinity of Pakistan Research Reactor - 1 (PARR-1) during 2007-2009. 41Ar was determined in the neutron activation analysis laboratory, Chemistry Division, PINSTECH during its normal spectra acquisitions. Initially, the peak at 1293.7 keV went un-identified but recently it has been associated with 41Ar. Although, the source of 41Ar is known, which is PARR-1 but its pathway into the laboratory is unknown. Moreover, the rate of production of 41Ar and the dose produced by it is also not known. The presence of a strong peak at 1293.7 keV not only masks the 1292.6 keV γ-line of 59Fe but it also increases the limit of detection for most of radionuclides. Its presence, therefore, should be taken seriously for neutron activation analysis work and for low-level countings.